Effect of Methanol Stem Bark Extract of Annona senegalensis as an Antibacterial Agent and on Liver Enzyme Markers in Diethyl Nitrosamine-Induced Hepatocellular Carcinoma in Rats - Umaru, Isaac John; Efongwa, Emmanuel; Omolara, Mosugu Ovayoza; Okang, Ogar Fonne; Akem, Ingwu Joseph; Tansaba, Akafa Andes; Philip, Shadrach; Frank, Otashu Kenneth (African Journal of Medicine, Surgery and Public Health Research, 2025)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide, frequently linked to exposure to chemical carcinogens such as diethylnitrosamine (DEN). Medicinal plants have emerged as promising sources of bioactive compounds with potential anticancer and antimicrobial properties. This study evaluated the therapeutic potential of methanol stem-bark extract of Annona senegalensis against DEN-induced hepatocellular carcinoma and selected bacterial pathogens. Fifty-four male albino rats were allocated into six groups, with hepatocarcinogenesis induced by DEN, followed by a 14-day treatment with varying doses of the extract. Hepatoprotective effects were assessed using liver enzyme markers and serum protein levels, while antibacterial activity was determined via disc diffusion assays against Staphylococcus aureus and Escherichia coli. Results demonstrated that the extract significantly reduced liver enzyme levels (ALT, AST, ALP) and improved serum proteins (total protein and albumin) at higher doses (400 and 600 mg/kg), indicating hepatoprotective potential. Bilirubin levels also improved, suggesting reduced liver stress. Antibacterial evaluation revealed dose-dependent activity, with strong inhibition against S. aureus comparable to tetracycline at 200 µg/mL, and moderate efficacy against E. coli. These findings highlight the dual therapeutic potential of A. senegalensis stem-bark extract as both a hepatoprotective and antibacterial agent. Future studies are recommended to isolate and characterize the bioactive compounds responsible for these effects and to expand antibacterial evaluation to a wider spectrum of pathogens.